Effectiveness of Polidocanol in the Treatment of Venous Malformations: A Meta-Analysis - Hu, Wei; Liu, Zhuang; Sun, Jiali; Wang, Liang; Song, Dan; Guo, Lei (Frontiers in Pediatrics, 2022)
Abstract Objective The aim of this study was to investigate the efficacy of polidocanol against venous malformations (VMs). Methods Studies reporting the treatment of VMs using polidocanol (published until February 15, 2020) were reviewed in the Embase and PubMed databases. After excluding the same literature, part of the studies were excluded by reading the title, abstract, full text. Eleven studies (with 305 participants) that fulfilled the inclusion criteria were included. Systematic meta-analysis was performed using Stata version 12.0, and a random-effects model was used to calculate the pooled effective rate of polidocanol against VMs and the 95% confidence intervals (CI). Results Lesion reduction of more than 50% was considered effective. A total of 305 patients were treated, and treatment in 271 was considered effective. The efficacy of polidocanol was 97% (95% CI = 0.945–0.992). Heterogeneity among the studies was small (I2 = 32.1%, P=0.142). The Begg’s test did not reveal any significant publication bias (P =0.815); however, the Egger's test did (P = 0.001, 95% CI=15.15–38.58). The funnel plot was roughly symmetric. Conclusion Our study suggested that polidocanol is effective in the treatment of VMs. VMs at different sites can be treated without serious complications. Therefore, we have reason to believe that polidocanol is a safe and an effective drug for VMs